PENYULINGAN DAN ANALISIS BEBERAPA JENIS MINYAK GANDAPURA - Ma’mun Ma’mun (Pusat Penelitian dan Pengembangan Perkebunan, 2005)
The distillation and analysis of wintergreen oil. Wintergreen oil is obtained by steam distillation of herbaceous plant of Gaultheria sp. The main compound of wintergreen oil is methyl salycilate which is used in pharmaceutical, perfume and fragrance, food and beverages industries. Methyl salycilate is also made synthetically by esterification reaction between methanol and salycilic acid with concentrated sulfuric acid as catalytic agent. So far, Indonesia still impor wintergreen oil, meanwhile at the local farmer level wintergreen oil is produced by using traditional distillation methode. Wintergreen plant growth at the highland. The experiment was conducted on the distillation wintergreen of large leaf type from Dieng Wonosobo Central Java, from Gunung Gede West Java and small leaf type from Sukamulya West Java. The oil characteristis produced was evaluated and compare to the characteristics of local oil, imported and synthetic oil. The result showed that the oil yield of large leaf type from Dieng Wonosobo is 0.80 %, from Gunung Gede is 1,20 %, small leaf type is 0,05 % and local distillation is 0,10 %. The methylsalycilate content of those oils are 97,41 %, 85,18 %, 38,20 % and 82,23 % respectively. The imported oil and synthetic oil have 98,40 % and 97,00 % methylsalycilate content. In general the oil characteristics of large leaf type from Dieng Wonosobo is almost the same to imported oil and meet the Indonesian National Standard.